Pengaruh Gaji, Tunjangan Kesejahteraan dan Kompensasi Terhadap Produktivitas Kerja Karyawan pada PT. Pos Indonesia Kantor Pos Wonogiri - Nugroho, Budi Setyo, Dr. Triyono, SE, M.Si (2017)
The purpose of this study was to determine the effect of salaries, welfare benefits and compensation for work productivity of employees at PT. Pos Indonesia Wonogiri Post Office. In this study, the sampling technique used is Confinient Sampling. Data types and sources of data in this study using primary data obtained from the respondents that are the result of filling out the questionnaire. Data analysis techniques used are validity with all the variables declared valid by the value corrected item-total correlation of each variable above .254, reliability test with the test results of this study each variable is declared reliable by Cronbach Alpha above .600. With the criteria that the employee's productivity and variable salaries, welfare benefits and compensation is positive and the impact on employee productivity, hypothesis testing by t-test at a variable salary, welfare benefits and significant compensation. F test on each variable and significant effect R2sebesar test results of 45.1% and the rest is explained by other variables amounted to 54.9%. It can be concluded that employees of PT. Pos Indonesia Wonogiri Post Office requires salaries, welfare benefits and compensation to improve the productivity of the work that so as to achieve goals and objectives of the company well. Keywords: Salaries, Allowances welfare, Compensation, and Employee Productivity